2010
DOI: 10.1021/jo100172t
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of the Reaction Mechanisms of Nitroxyl and Thiols

Abstract: Nitroxyl, or nitrosyl hydride, (HNO) is a pharmacologically relevant molecule whose physiological responses have been thought to result from modification of intracellular thiols. The reaction of HNO with thiols has been shown to lead to disulfides and sulfinamides. The free energies of reaction (DeltaG) and activation (DeltaG(++)) were determined for the reaction pathways of HNO and five different thiols using computational methods. The methods employed included B3LYP, MP2, and CBS-QB3, as well as IEF-PCM to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Possible targets for HNO are cysteine residues within GLUT1 itself. Previous work in erythrocytes has shown that GLUT1 can be activated by disulfide bond formation within GLUT1 [31], and computational studies have indicated that within a hydrophobic environment such as the cell membrane, the disulfide product of HNO reaction with cysteine residues is the preferred product over the sulfinamide [38]. It is not known if HNO is the actual agent responsible for physiological activation of GLUT1 or if this is purely a pharmacological phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible targets for HNO are cysteine residues within GLUT1 itself. Previous work in erythrocytes has shown that GLUT1 can be activated by disulfide bond formation within GLUT1 [31], and computational studies have indicated that within a hydrophobic environment such as the cell membrane, the disulfide product of HNO reaction with cysteine residues is the preferred product over the sulfinamide [38]. It is not known if HNO is the actual agent responsible for physiological activation of GLUT1 or if this is purely a pharmacological phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…However, in support of this mechanism, we have found that two thiol-active agents, phenylarsine oxide [35] and cinnamaldehyde [36], activate glucose uptake in L929 fibroblast cells, a cell line that express only the GLUT1 isoform [37]. If GLUT1 is activated in L929 cells in a manner similar to erythrocytes, we would predict that HNO would trigger a disulfide bond formation in GLUT1, which appears to be the preferred HNO-induced product in a hydrophobic environment [38], and thereby activate glucose uptake. Therefore, the specific purpose of this study was to systematically investigate the acute effects of Angeli’s salt (AS), an in situ producer of HNO, on glucose uptake in L929 fibroblast cells.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the biological significance of HNO reactions with thiols, a recent computational investigation was performed on five different thiols, RSH with R=H, CH 3 , CF 3 , Ph, and cysteine to specifically address issues of hydrophobicity of the environment, the availability of a local base, and the identity of the thiol substituent on the HNO reactivities [81]. The first step is the same for different R groups, from RSH to RSNHOH (similar to reaction 4 ), which then undergoes two different reaction pathways, A and B, to form sulfonamide (RSONH 2 ) and disulfide (RSSR), respectively, as shown in Fig.…”
Section: Hno Reactions With Biologically Important Non-metal Systemsmentioning
confidence: 99%
“…Recent experimental and computational analyses of these interactions have clarified mechanistic details (60,148,149). High-performance liquid chromatography detection of sulfinamide has also been offered as an indicator of HNO production (34).…”
Section: ð4þmentioning
confidence: 99%